The Revised Ordinances of the City of Portland 22 (1848) - (:unkn) unknown (My University, 1848)
§§ 1-2: No person not licensed to keep and sell gunpowder shall keep or have in his shop, store, dwelling house or other tenement, at any one time, a larger quantity of gunpowder than one pound. § 2. No person licensed to keep and sell gunpowder shall have or keep in his store, shop, dwelling house or in any other tenement or place whatever at any one time, a larger quantity of gunpowder then twenty-five pounds.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER